Exploring the Relationship between Financial Literacy and Consumer Communication in Financial Decision-Making: A Study of English Literature Student - Ruth Keitaro Maureen Naibaho; Shinta Melina Sidabutar; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores the relationship between financial literacy, consumer communication, and financial decision-making among English Literature students at Universitas Negeri Medan. Using surveys with 40 participants aged 20-24, the research assesses students’ financial literacy levels, preferences for communication formats, and their impact on financial behaviors. Rsults indicate that while most students have a basic understanding of financial concepts, gaps exist in budgeting, selecting financial products, and seeking assistance. Visual formats like videos and infographics are the preferred communication channels, while social media, though widely accessed, often lacks clarity. Only a portion of students applies financial literacy effectively in decision-making, such as evaluating financial products critically or avoiding unnecessary spending. The findings emphasize the importance of integrating tailored financial education programs with effective communication strategies. Enhancing financial literacy through practical and accessible learning methods can empower students to make informed and strategic financial decisions.